A two-level model of information units with complex structure that correspond to the questioning metaphor - Gribova, V. V.; Kleshchev, A. S.; Moskalenko, F. M.; Timchenko, V. A. (Automatic documentation and mathematical linguistics, 2015)
A two-level model of information units is described. It can be used as a basis for computer tools for editing information with a complex structure with different levels of abstraction and invariance to technological spaces (subject domains) in a common conceptual framework for carriers of this information. Using editing tools which are based on this model makes it unnecessary to organize specialized training for these carriers or to involve professional intermediaries.